PERBANDINGAN HARGA SAHAM SEBELUM DAN SELAMA PANDEMI COVID-19 (Studi Pada Saham LQ 45 di Bursa Efek Indonesia) - irianto Irianto; Baiq Kisnawati; Istiarto Istiarto (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2021)
This study aims to determine the difference in LQ45 stock prices before and during the Covid-19 pandemic on the Indonesia Stock Exchange. This type of research is comparative research. The population is 45 companies classified as LQ45 on the Indonesia Stock Exchange. Determination of the sample by purposive sampling, selected as many as 39 companies that are classified as LQ45. The data used is quantitative data sourced from publications on the Indonesia Stock Exchange. The data analysis technique used the Two-Mean Difference Test. The results showed that there was no significant difference in the price of LQ45 before the pandemic and during the Covid-19 pandemic Keywords: stock price, LQ45 stock, Covid-19 pandemic